Emergency peripartum hysterectomy and its association with cesarean section: a 3 years retrospective study - Kaur, Harpreet; Kaur, Balpreet; Kaur, Sarvjeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency peripartum hysterectomy refers to the abdominal hysterectomy performed during or immediately after cesarean section or vaginal delivery, in a setting of life threatening haemorrhage. Over the past two decades, incidence of cesarean section has greatly increased which emerges as one of the cause for abnormal placentation in subsequent pregnancies thus resulting in increased incidence of haemorrhage. The unplanned nature of the surgery and acute blood loss renders the patient in a less than ideal situation to undergo such a dramatic surgery. Evaluation of risk factors, adequate resuscitation, involvement of senior obstetrician and timely decision for EPH in cases of refractory peripartum haemorrhage would help in significantly reducing the maternal mortality and morbidity. Objective was to study the association between cesarean section and emergency peripartum hysterectomy. Methods: It is a retrospective study of all women who had undergone emergency peripartum hysterectomy between January 2015 to January 2018 in the Department of Obstetrics and Gynaecology, Guru Gobind Singh Medical College, Faridkot. Incidence, indications, risk factors and complications of emergency peripartum hysterectomies (EPH) were recorded. Results: During three years period the overall incidence of EPH was 1.85 per 1000 deliveries. Conclusions: Emergency peripartum hysterectomy is a challenging procedure performed in obstetrics when all other conservative methods to control uterine haemorrhage have failed. With increased incidence of cesarean sections the cause of emergency peripartum hysterectomy has greatly shifted from uterine atony to abnormal placentation. Abnormal placentation has now become the most commonly associated indication for EPH. Recognising and assessing patients at risk with appropriate and timely intervention would help in ensuring a better outcome in this otherwise difficult situation.